2008
DOI: 10.1097/mao.0b013e31816c7c25
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Vestibular Evoked Myogenic Potentials in Healthy Subjects

Abstract: Overall, VEMP response parameters were found to have fair to good test-retest reliability. The intraclass correlation coefficient value for amplitude was found to be more reliable than latency, with the latency of n23 more reliable than the latency of p13. Clinicians should consider these findings when interpreting VEMP responses. Maintenance of symmetric head rotation with and without EMG monitoring produced reliably reproducible results, the VEMP amplitude being the best criteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
61
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(71 citation statements)
references
References 8 publications
7
61
0
3
Order By: Relevance
“…The first method is the monitoring of the pre-stimulus contraction level of the SCM, so the system runs a correction algorithm capable of calculating corrected amplitudes or it does not accept the myogenic responses if level of contraction is out of a pre-defined range [14,19]; the second is the use of a visual feedback system as a blood pressure manometer [16,19] or a visual display to maintain a steady contraction during the test. In our experiments, we have used both methods to monitor the level of tonic contraction in the SCM between different trials.…”
Section: Reliability Of Vempsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first method is the monitoring of the pre-stimulus contraction level of the SCM, so the system runs a correction algorithm capable of calculating corrected amplitudes or it does not accept the myogenic responses if level of contraction is out of a pre-defined range [14,19]; the second is the use of a visual feedback system as a blood pressure manometer [16,19] or a visual display to maintain a steady contraction during the test. In our experiments, we have used both methods to monitor the level of tonic contraction in the SCM between different trials.…”
Section: Reliability Of Vempsmentioning
confidence: 99%
“…Although the reliability of STB-induced VEMPs has been investigated [13][14][15][16][17], a comparative study of individual responses to STB-and clicks-induced VEMPs in a group of healthy subjects has not been carried out and there is no rationale for using either click or STB. To solve this issue, we performed a reliability study for STB-and click-induced VEMPs in healthy subjects in different sessions.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent report, evaluation of VEMP responses with or without the use of EMG monitoring in two separate sessions was studied. It was found that symmetric head rotation with and without EMG monitoring produced reliably reproducible results [50]. However, the sample is small, only 20 participants, and further studies are needed to verify this statement.…”
Section: Monitoring Of Scm Contractionmentioning
confidence: 88%
“…Although the EMG was not monitored, it was made sure that the cVEMP waveforms were visually monitored for any insufficient strength of neck contraction. Interestingly, Isaradisaikul et al (2008) reported that there was no significant difference between the cVEMP waveforms with and without EMG monitoring.…”
Section: Comparisons Between Stimulus Durationmentioning
confidence: 99%